The Metabolic Profile of Tumor and Virally Infected Cells Shapes Their Microenvironment Counteracting T Cell Immunity - Magalhaes, Isabelle; Yogev, Ohad; Mattsson, Jonas; Schurich, Anna (Frontiers in Immunology, 2019)
Upon activation naïve T cells undergo metabolic changes to form different subsets of effector or regulatory cells, and subsequently remodel their metabolic profile again to form memory. Interfering with these metabolic alterations leads to abrogation or reprogramming of T cell differentiation, demonstrating the importance of this pathway in T cell development. It has long been appreciated that the conversion of a healthy cell to a cancerous cell is accompanied by metabolic changes, which support uncontrolled proliferation. Especially in solid tumours these metabolic changes significantly influence the tumour microenvironment (TME) and affect tumour infiltrating immune cells. The TME is often hypoxic and nutrient depleted, additionally tumour cells produce co-inhibitory signals, together supressing the immune response. Interestingly, viruses can stimulate a metabolism akin to that seen in tumour cells in their host cells and even in neighbouring cells (e.g. via transfer of virally modified extracellular vesicles). Thus viruses create their own niche which favours viral persistence and propagation, while again keeping the immune response at bay. In this review we will focus on the mechanisms employed by tumour cells and viruses influencing T cell metabolic regulation and the impact they have on shaping T cell fate.